The Implementation of Project-Based Learning in Teaching Descriptive Writing Based on Local Wisdom at MAN 3 Cirebon - Aghitsni Maulaya; Rahayu Puji Haryanti (Universitas Islam Negeri Palopo, 2026)
Previous research on project-based learning (PBL) in descriptive writing has largely examined writing outcomes or local-wisdom content within a single cultural setting. Less attention has been given to how PBL is implemented when students from different regional backgrounds use diverse local-wisdom topics to produce an authentic text-based product in an Indonesian Islamic senior high school. This qualitative case study investigated the implementation and challenges of local-wisdom-based PBL in a tenth-grade descriptive writing class at MAN 3 Cirebon. Participants were one English teacher and 33 students; 32 students participated in follow-up interviews. Data were obtained from four classroom observations, semi-structured interviews, lesson and project documents, students’ descriptive texts, and six tourism brochures. The data were analyzed thematically and compared across sources. The findings show that the project proceeded through orientation and topic selection, collaborative planning and information gathering, drafting and peer-supported revision, brochure design, presentation, and reflection. Student choice, division of roles, peer assistance, and culturally familiar topics supported active participation and helped students elaborate content, organize information, and attend to vocabulary and grammatical form. Local-wisdom topics also enabled students to connect English writing with cultural knowledge and representation. The main challenges were limited classroom time, uneven participation, restricted vocabulary and grammatical control, and difficulty expressing culturally specific meanings in English. The study indicates that culturally grounded PBL can provide a meaningful framework for descriptive writing when accompanied by explicit language scaffolding, structured group accountability, and realistic project scheduling